2020
DOI: 10.26628/wtr.v91i12.1084
|View full text |Cite
|
Sign up to set email alerts
|

Condition monitoring of crack extension in the reinforcement adhesive joints by carbon nanotubes

Abstract: Carbon nanotubes (CNT) are ideally suited to be employed for damage sensing in fiber rein- forced composite structures. In this work, the capability of CNTs for crack extension of a single lap Al-Al adhesive joints (SLJ) under shear load is studied using electrical resistance change. Different weight per- cent of CNT are added to epoxy adhesive. Epoxy adhesive with high concentration of CNT is obtained during shear loading to have the maximum strength and provide the best sensory propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…This results in the onset of delamination, which can lead to the rapid degradation of the mechanical performance of the structure and cause premature failure [9][10][11][12]. Accordingly, multiple studies have investigated methods for adhesive layer modification [13,14] or composite laminate modification to delay delamination in a composite joint [15][16][17], such as the use of fibre metal laminates (FML), composite laminates with toughened layers [18,19], glass fabric reinforcement [20], the use of Z-pins [21,22], 3D weaving [23], stitching [23], braiding [24], or even the adoption of additional thermoplastic inter-plies [25]. However, the significant complexity of these techniques often restricts their usage.…”
Section: Introductionmentioning
confidence: 99%
“…This results in the onset of delamination, which can lead to the rapid degradation of the mechanical performance of the structure and cause premature failure [9][10][11][12]. Accordingly, multiple studies have investigated methods for adhesive layer modification [13,14] or composite laminate modification to delay delamination in a composite joint [15][16][17], such as the use of fibre metal laminates (FML), composite laminates with toughened layers [18,19], glass fabric reinforcement [20], the use of Z-pins [21,22], 3D weaving [23], stitching [23], braiding [24], or even the adoption of additional thermoplastic inter-plies [25]. However, the significant complexity of these techniques often restricts their usage.…”
Section: Introductionmentioning
confidence: 99%
“…The contact between the adherends and the punch was modelled using the surface-to-surface contact method with the penalty algorithm and the hard contact model. The goal of this paper is to elucidate the complex failure process of the adhesive layer in stepped lap joints in different configurations under bending loading [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is crucial to develop a strong interfacial adhesion to correctly transfer the load from the polymeric matrix to the nano-reinforcement [13]. Carbon-based nanoparticles, such as carbon nanofibers (CNFs), carbon nanotubes (CNTs) and graphene nanoplatelets (GNPs), are widely used for this purpose [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. These nanoparticles enhance the fatigue life of bonded joints and can be used for damage detection, as they also improve the electrical properties of the resin they are dispersed in [29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-based nanoparticles, such as carbon nanofibers (CNFs), carbon nanotubes (CNTs) and graphene nanoplatelets (GNPs), are widely used for this purpose [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. These nanoparticles enhance the fatigue life of bonded joints and can be used for damage detection, as they also improve the electrical properties of the resin they are dispersed in [29][30][31][32][33][34][35][36][37][38][39]. Recently, studies have shown that the application of hybrid nanoparticles is a viable approach to designing tougher, stronger and more durable bonded joints [40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%